Management of Business EthicsSufrinSidney C.. Management of Business Ethics. Port Washington, N.Y.: Kennikat Press, 1980, 125 pp., $12.50. - Johnson, Harold (Academy of Management Review, 1980)
The article reviews the book ?Management of Business Ethics,? by Sidney C. Sufrin.